The art of vanishing [large type] - Kuhn, Cynthia G., 1965- (A Lila Mclean Academic Mystery, 2018)
When Professor Lila Maclean is sent to interview celebrated author and notorious cad, Damon Von Tussel, he disappears before her eyes. Chaos ensues, as Damon is headlining Stonedale University's Art Week.The chancellor expects Lila to locate him and set events back on track. But someone has a different plan. Strange warnings, missing valuables, and dangerous incidents are plaguing Stonedale's guests. With her mother, who happens to be Damon's ex, in harm's way, Lila must bring the culprit to light before anything or anyone else vanishes.